2015
DOI: 10.1121/1.4920150
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive monitoring of valve bodies utilizing spray-on transducer technology

Abstract: Structural health monitoring (SHM) and non-destructive evaluation (NDE) can be performed both actively and passively. Active monitoring is useful for thickness measurement and crack interrogation. Passive monitoring can indicate integrity of the valve and if it is open or closed. Traditional SHM methods for valve bodies require a bonding medium that can deteriorate. A sol-gel spray-on technology eliminates the need for a coupling medium since the transducer is chemically bonded to the valve body. These spray-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A table of candidate materials for longitudinal wave generation is provided below in Table 3; however, this is only the first step. The final column in Table 3 is of substantial importance as it has been found that crystal structure plays a significant role in radiation tolerance of ceramics [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74].…”
Section: Piezoelectric Materials For Radiation Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A table of candidate materials for longitudinal wave generation is provided below in Table 3; however, this is only the first step. The final column in Table 3 is of substantial importance as it has been found that crystal structure plays a significant role in radiation tolerance of ceramics [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74].…”
Section: Piezoelectric Materials For Radiation Environmentmentioning
confidence: 99%
“…During the past decades there has been significant interest and therefore research into the problem of ultrasonic transducers for harsh environments [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,…”
Section: Introductionmentioning
confidence: 99%